Membangun Hubungan Positif di Pesantren: Pilar Utama Pendidikan Positif dalam Konteks Pesantren - Muhammad Iwa Sambada Dzikrullah; Siti Rohmah Nurhayati; Hazalizah Hamzah (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
Theoretically, positive relationships are found in several positive education concepts such as PERMA, PROSPER, EPOCH, and SEARCH, each with its own theoretical characteristics, but all aim to improve a person's well-being. In practice, positive relationships can be realized in various forms, for example in friendships, the workplace, family, and education. One form of education that is uniquely traditional in Indonesia is the Islamic boarding school (pesantren). Examining positive relationships in Islamic boarding schools requires an indigenous approach to view positive relationships in their context. Research on positive education in Islamic boarding school education culture is still underexplored, especially on the issue of positive relationships, which is one of the points of significant difference from other educational cultures, both in Indonesia and abroad. Therefore, this study aims to explore the form of positive education, and more specifically, positive relationships, using indigenous psychology in Islamic boarding school education culture. This study uses a qualitative approach and data collection using an open-ended questionnaire involving 177 students as participants. Data analysis used thematic analysis to produce meaningful patterns from the existing data set. The results of this study indicate that positive relationships formed within the Islamic boarding school culture are between students and their kyai (Islamic clerics), mentors, teachers, and fellow students. The outcomes of these relationships within the students include a sense of security and self-confidence, resilience and positive orientation, self-regulation and personal wisdom, social concern and altruism, a sense of togetherness, social awareness, and interpersonal skills.